The epidemiology of skin conditions in the aged: A systematic review - Hahnel, Elisabeth; Lichterfeld, Andrea; Blume-Peytavi, Ulrike; Kottner, Jan (Journal of tissue viability, 2017)
The human population is aging. A systematic summary of the epidemiology of skin diseases in the aged is lacking. A systematic review was conducted including electronic database searches in MEDLINE, Embase, SCOPUS and Web of Science. The eligibility criteria were primary incidence and prevalence studies or secondary data analysis, English or German language, subjects being 65+ years and reported skin problems or diseases. Data extraction was conducted using a standardized data collection form and the methodological quality of included studies was assessed. After screening of 1491 records, 74 records were included reporting data for more than 20 skin conditions. The majority of prevalence and incidence figures was identified for hospital and long-term care settings. The most prevalent skin diseases were fungal infections (14.3%–64%), dermatitis (1%–58.7%), xerosis (5.4%–85.5%) and benign skin tumors (1.7%–74.5%). Additionally, pressure ulcer prevalence ranged from 0.3% to 46% and incidence from 0.8% to 34%. Skin conditions and diseases in aged populations are frequent. Health care practitioners should pay attention to those, although skin conditions might not be the primary reason for seeking care. Epidemiological data are lacking especially for home care and community settings although this can be regarded as the most important from a public health and prevention point of view. The methodological quality and reporting of epidemiological studies in the aged populations must be improved. CRD42014014553 (PROSPERO). •Aging increases the susceptibility to adverse skin conditions and diseases.•Skin diseases in aged populations are prevalent.•Epidemiological figures are lacking for home care and community settings.•Skin preventive strategies from a public health perspective are warranted.